2016
DOI: 10.1158/1078-0432.ccr-15-1990
|View full text |Cite
|
Sign up to set email alerts
|

Low Cancer Stem Cell Marker Expression and Low Hypoxia Identify Good Prognosis Subgroups in HPV(−) HNSCC after Postoperative Radiochemotherapy: A Multicenter Study of the DKTK-ROG

Abstract: Purpose: To investigate the impact of hypoxia-induced gene expression and cancer stem cell (CSC) marker expression on outcome of postoperative cisplatin-based radiochemotherapy (PORT-C) in patients with locally advanced head and neck squamous cell carcinoma (HNSCC).Experimental Design: Expression of the CSC markers CD44, MET, and SLC3A2, and hypoxia gene signatures were analyzed in the resected primary tumors using RT-PCR and nanoString technology in a multicenter retrospective cohort of 195 patients. CD44 pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
143
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 116 publications
(166 citation statements)
references
References 53 publications
(67 reference statements)
11
143
2
2
Order By: Relevance
“…The importance of inactivation of CSC by radiotherapy for local tumor control is supported by a number of further experiments (38) and recent clinical data, for example, for patients with early stage laryngeal cancer using the putative CSC marker CD44 (36, 39), CSC number correlated with permanent local tumor control. In line with this result, a multicenter retrospective analysis of postoperative radiochemotherapy in HPV-negative high-risk HNSCC revealed a significant correlation between high levels of CD44 protein expression as well as mRNA expressions of other putative CSC markers and low locoregional tumor control after radiochemotherapy (40). A further example is the observation that low 26S proteasome activity, which leads to CSC-like phenotype with higher self-renewal capacity and higher tumorigenicity, correlates with locoregional control in HNSCC (41).…”
Section: Focus Areas: Preclinical Radiobiological Assaysmentioning
confidence: 57%
“…The importance of inactivation of CSC by radiotherapy for local tumor control is supported by a number of further experiments (38) and recent clinical data, for example, for patients with early stage laryngeal cancer using the putative CSC marker CD44 (36, 39), CSC number correlated with permanent local tumor control. In line with this result, a multicenter retrospective analysis of postoperative radiochemotherapy in HPV-negative high-risk HNSCC revealed a significant correlation between high levels of CD44 protein expression as well as mRNA expressions of other putative CSC markers and low locoregional tumor control after radiochemotherapy (40). A further example is the observation that low 26S proteasome activity, which leads to CSC-like phenotype with higher self-renewal capacity and higher tumorigenicity, correlates with locoregional control in HNSCC (41).…”
Section: Focus Areas: Preclinical Radiobiological Assaysmentioning
confidence: 57%
“…Radiobiologic studies provided evidence for the importance of these cells for local tumor control and suggested that efficient tumor treatment by irradiation might require eradication of the entire CSC population. The role of CSCs in tumor development and recurrence has recently motivated investigations of CSCspecific biomarkers for the analysis of CSC populations in tumor pretreatment biopsies for the prediction of clinical outcome and selection of the optimal treatment strategy (13,14). It is also assumed that the combination of radiotherapy with agents that target or radiosensitize the CSC population might be beneficial for the treatment refinement (14).…”
Section: Introductionmentioning
confidence: 99%
“…The role of CSCs in tumor development and recurrence has recently motivated investigations of CSCspecific biomarkers for the analysis of CSC populations in tumor pretreatment biopsies for the prediction of clinical outcome and selection of the optimal treatment strategy (13,14). It is also assumed that the combination of radiotherapy with agents that target or radiosensitize the CSC population might be beneficial for the treatment refinement (14). However, compelling evidence suggests a high diversity of CSCs and plasticity of their features imposed by tumor treatment, which could challenge the development of CSC-related predictive biomarkers and CSC-targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their key role in primary tumor growth and maintenance, CSCs have a high competence to evade the effects of radiotherapy and conventional chemotherapy and play an integral role in treatment resistance leading to local recurrence and distant relapse [44]. Expression patterns of CSC markers and hypoxia-related genes were recently assessed in a multicenter, retrospective cohort study and correlated with treatment outcome after postoperative radiochemotherapy [45]. Detection of low CSC marker expression identified a subgroup of HPVnegative HNSCC with good prognosis and might support stratification of patients for individualized treatment de-escalation in future clinical trials.…”
Section: The Concept Of Cancer Stem-like Cellsmentioning
confidence: 99%